Modeling of Coal Deposition Using the Resistivity Method with Wenner Configuration in the Bentarsari Basin Area, District of Salem, Brebes Regency, Central Java: Putri Suci Ramdani, Muhammad Sehah - Putri Suci Ramdani Putri Suci Ramdani; Sehah Sehah (Jurnal Fisika dan Aplikasinya, 2021)
Research to model coal deposits in the Bentarsari Basin area of Salem District in Brebes Regency has been done using the geoelectric-resistivity method with Wenner configuration. Resistivity data acquisition is carried out on five tracks, with each track has a length of 200 m. The least squares inversion method is applied to obtain a 2D-resistivity section model. Furthermore, the 2D-resistivity section model data for each line is combined into a 3D model to determine the coal deposit model in the area. The results of the interpretation indicate that the subsurface structure of the area consists of clay, sandy clay, coal, and sandstone; where the type of coal is lignite. This coal deposit has resistivity values with interval of 86.1 – 219.0 0m, which is distributed evenly with depth of 0.0 – 26.5 m, where the southern part of the all track has a higher potential. This research can be followed up with log drill testing to determine the actual subsurface layer, so that it can be utilized as a very economical alternative energy.